How Teachers Become “Good” At What They Do A Narrative Approach - Idhun Wirawati; Fitri Kurniawan (Jurnal VARIDIKA, 2015)
The research was purposed to explore how teachers learn from their professional experience to become ‘good’ at what they do.  The research was a replication of the a study project conducted by School of Education at University of Aberdeen in 2012 . The current research was an effort to investigate the teachers’ learning from their professional experience in different context and participants. The study is an interpretation of narratives of two primary school teachers from SD Muhammadiyah Klaten Utara, Indonesia. The narratives materials are taken from the research project undertaken in Klaten jointly conducted by the Department of Education at Universitas Muhammadiyah Surakarta and SD Muhammadiyah Klaten Utara. This study is a narrative reseach approach. The analysis in this report is  using  narrative  approach  because  the  materials  are  the  narratives  of  two  teachers  of primary teachers. The finding shows that two things that makes them become good teacher.  The first one is the teacher’s will to always learn from problems they faced. Their persistent concern to make a positive rapport with children and parents